2020
DOI: 10.26508/lsa.202000670
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular characterization of multicomponent resistance ofPseudomonasagainst allicin

Abstract: The common foodstuff garlic produces the potent antibiotic defense substance allicin after tissue damage. Allicin is a redox toxin that oxidizes glutathione and cellular proteins and makes garlic a highly hostile environment for non-adapted microbes. Genomic clones from a highly allicin-resistant Pseudomonas fluorescens (PfAR-1), which was isolated from garlic, conferred allicin resistance to Pseudomonas syringae and even to Escherichia coli. Resistance-conferring genes had redox-related functions and were on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 105 publications
1
22
0
Order By: Relevance
“…A strong association between the genetic requirements for the bacterium Pantoea ananatis to colonize necrotized onion tissues and its capacity for tolerance to the thiosulfinate allicin has been found based on the presence of an eleven-gene, plasmid-borne, virulence cluster of sulfur redox genes in the bacterial genome [192]. Furthermore, genomic clones from a highly allicin-tolerant bacterium Pseudomonas fluorescens isolated from garlic conferred allicin tolerance to Pseudomonas syringae [193]. In addition, methyl methanethiolsulfinates, the hydrolysis products of S-Methyl-l-cysteine sulfoxide, have been shown to be important antibacterial compounds in cabbage effective against Leuconostoc mesenteroides [194,195].…”
Section: Thiosulfinatesmentioning
confidence: 99%
“…A strong association between the genetic requirements for the bacterium Pantoea ananatis to colonize necrotized onion tissues and its capacity for tolerance to the thiosulfinate allicin has been found based on the presence of an eleven-gene, plasmid-borne, virulence cluster of sulfur redox genes in the bacterial genome [192]. Furthermore, genomic clones from a highly allicin-tolerant bacterium Pseudomonas fluorescens isolated from garlic conferred allicin tolerance to Pseudomonas syringae [193]. In addition, methyl methanethiolsulfinates, the hydrolysis products of S-Methyl-l-cysteine sulfoxide, have been shown to be important antibacterial compounds in cabbage effective against Leuconostoc mesenteroides [194,195].…”
Section: Thiosulfinatesmentioning
confidence: 99%
“…The strain and its resistance-features will be discussed in more detail in Section 3 , however, the strain had three glutathione reductase ( gor ) genes compared to the single copy in the closely related but less tolerant Pf 0-1 strain. The higher gene copy number reflected a 2-fold higher Gor enzyme activity in Pf AR-1 compared to Pf 0-1 [ 77 ]. In the same study it was demonstrated that an E. coli Δ gor mutant, which showed an increased susceptibility to allicin compared to the wild type, could be complemented by expression of a heterologous Pf AR-1 gor gene.…”
Section: Allicin and Oxidative Stress In Cells And Organismsmentioning
confidence: 99%
“…We isolated and investigated a P. fluorescens isolate from garlic which showed an exceptionally high level of allicin resistance compared to other bacteria. We named this isolate P. fluorescens Allicin Resistant-1 ( Pf AR-1) [ 77 ]. A Pf AR-1 genomic library was prepared and shotgun transferred into an allicin-sensitive P. syringae strain.…”
Section: Transcriptomic and Proteomic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several mechanisms that contribute to the resistance to allicin in bacteria like the Mercuric reductase MerA proteins, which seem to be able to detoxify allicin by reduction. A genomic cluster conveying the resistance has been identified employing a highly allicin-resistant Pseudomonas fluorescens strain isolated from garlic [9]. Recently, allicin, because of its oxidizing nature, has been reported to induce apoptosis in yeast cells [8], an alternative cell-killing mechanism to the formerly suggested specific oxidative inactivation of crucial enzymes [10,11].…”
Section: Introductionmentioning
confidence: 99%